2022
DOI: 10.1186/s12893-022-01752-3
|View full text |Cite
|
Sign up to set email alerts
|

The clinical features of late postoperative cholangitis following pancreaticoduodenectomy brought on by conditions other than cancer recurrence: a single-center retrospective study

Abstract: Background Postoperative cholangitis is a late complication of pancreaticoduodenectomy (PD). This study aimed to elucidate the pathogenesis of post-PD cholangitis (PPDC) and explore its optimal treatment. Methods We retrospectively analyzed 210 patients who underwent PD at our institute between 2009 and 2018. Patients who underwent follow-up for less than 1 year or had cholangitis caused by cancer recurrence were excluded from the analysis. Diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…POC is one of the early and late complications after PD, with a reported frequency of 5.7%-21.1%. 3,4,[9][10][11][12] In the present study, total POC, E-POC, and L-POC occurrence were 26, 15.4, and 14.8%, respectively; hence, these results align with the results of previous studies. POC after PD sometimes occurs repeatedly, 3 sometimes increasing the length and cost of hospitalization.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…POC is one of the early and late complications after PD, with a reported frequency of 5.7%-21.1%. 3,4,[9][10][11][12] In the present study, total POC, E-POC, and L-POC occurrence were 26, 15.4, and 14.8%, respectively; hence, these results align with the results of previous studies. POC after PD sometimes occurs repeatedly, 3 sometimes increasing the length and cost of hospitalization.…”
Section: Discussionsupporting
confidence: 93%
“…One article reported that the median duration from PD to POC onset was 275 days (range, 30–3037) 3 . This duration was similar to our results; however, another study showed that the percentage of patients who experienced first‐episode POC more than 2 years after PD was 27% 10 . Hence, the occurrence of L‐POC may have increased if the follow‐up period of our study had been longer.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The long-term complications after PD have been reported as nutritional disorder, postoperative cholangitis due to bile duct resection, 81,82 and exocrine [83][84][85] and endocrine dysfunction, 86 and several studies on the comparisons of such long-term complications between the DPPR and PD groups are reported in Table 3.…”
Section: Clinical Advantage Of Dpphr Compared With Pancreaticoduodene...mentioning
confidence: 99%
“…The long‐term complications after PD have been reported as nutritional disorder, postoperative cholangitis due to bile duct resection, 81,82 and exocrine 83–85 and endocrine dysfunction, 86 and several studies on the comparisons of such long‐term complications between the DPPR and PD groups are reported in Table 3. Horiguchi et al 7 revealed that both exocrine (evaluated by the 13 C‐trioctanoin breath test) and endocrine functions (evaluated by HbA1c) were superior in the DPPHR group than in the PPPD group.…”
Section: Current Trend Of Dpphrmentioning
confidence: 99%